Beach Tourism Area Development Strategy. Case Study : Pancer Door Beach Pacitan â€“ East Java - Wulandari, Lisa Dwi; Ashgaf, Irfan Maulana (University of Merdeka Malang, 2023)
Well-known as â€œParadise of Javaâ€, Pacitan have a lot of coastal natural scenery and cultural attractions that potential to attract the tourist. One of the beach near town center of Pacitan as a main tourism destination is Pancer Door Beach. Even though have a lot of natural environment potential that interesting but this beach is less attractive to tourist to visit because of its natural potention, artificial, and cultural potention is not optimal. To explore further of the potential of Pancer Door Beach to be developed in the future, this research was carried out with a SWOT analysis approach to determine the internal and external factors that could be used as a development elements of this beach tourism. The stages of the research are exploring phenomena, interviewing keypersons and research respondents, direct observation of research objects related to the 4A tourism concept (attraction, accessibility, amenities, and ancilliary), then reviewing applicable regulations/standards/regulations to be cross-checked with theory and community needs, so it become the basis of the strategy for developing the Pancer Door Beach Tourism Area in the future.Keywords: Beach, Development Strategy, Potention, Tourism Attraction